2019
DOI: 10.1049/htl.2019.0008
|View full text |Cite
|
Sign up to set email alerts
|

Research on a physical activity tracking system based upon three‐axis accelerometer for patients with leg ulcers

Abstract: Venous leg ulcerations are a common problem, with high prevalence in the middle-aged and elderly population, and more attention on research of their physical activities has been paid, as they have great effects on the blood circulation of the lower limb. With enough, appropriate training, the chronic venous ulcerations in the lower limb can be avoided and alleviated, and venous hypertension can be reduced effectively. The study deals with a physical activity tracking system for the patients based on a three-ax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Domestic-related research is still focused on quantitative evaluation algorithm research, and commercial products have not been reported. Many foreign companies have carried out research and development of PD quantitative evaluation products, such as the Research Kit launched by Apple, which aims to provide corresponding interfaces for PD patient data collection [ 4 ]. Kinesia 360, a quantitative evaluation system for human motor function, was developed by Cleveland Medical Instrument Company in the United States, which adopted accelerometer and gyroscope sensors to record motion information; the device was worn on the wrist and fingers of patients to dynamically monitor upper limb motor dysfunction [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Domestic-related research is still focused on quantitative evaluation algorithm research, and commercial products have not been reported. Many foreign companies have carried out research and development of PD quantitative evaluation products, such as the Research Kit launched by Apple, which aims to provide corresponding interfaces for PD patient data collection [ 4 ]. Kinesia 360, a quantitative evaluation system for human motor function, was developed by Cleveland Medical Instrument Company in the United States, which adopted accelerometer and gyroscope sensors to record motion information; the device was worn on the wrist and fingers of patients to dynamically monitor upper limb motor dysfunction [ 5 ].…”
Section: Introductionmentioning
confidence: 99%